Micronutrients and skin cancer risk: a Mendelian randomization study - Wangcheng Chen; Lili Pang; Xiuzhen Wei; Yuemei Lan; Xiayi Su; Yaling Dong; Zhibo Zhu; Jie Bai; Jiayan Zhou; Heteng Cui; Baihong Zhang (World Journal of Surgical Oncology)
Abstract Background The intake of micronutrients is linked to cancer risk, but their specific mechanisms in skin cancer remain unclear. This study systematically investigated the causal effects of 15 micronutrients on non-melanoma skin cancer (NMSC) and malignant melanoma (MM) using Mendelian Randomization (MR). Methods Genetically predicted levels of 15 micronutrients served as instrumental variables in a two-sample MR analysis, utilizing data from the Finnish FinnGen database (version R10). To address potential horizontal pleiotropy and heterogeneity, sensitivity analyses included inverse-variance weighted (IVW), weighted median, MR Egger regression, and MR PRESSO. The study analyzed data from 650,657 European participants, including 19,077 NMSC and 3,194 MM cases. Results Selenium (p = 0.0001, OR 0.788, 95% CI 0.703–0.883) and Potassium (p = 0.045, OR 0.463, 95% CI 0.219–0.982) were significantly negatively associated with MM risk, suggesting a protective effect. Conversely, Calcium (p = 0.025, OR 1.257, 95% CI 1.030–1.534) was positively associated with NMSC risk, indicating it may be a risk factor. Vitamin B6 (p = 0.004, OR 0.741, 95% CI 0.604–0.909) also showed a significant protective effect against NMSC.The remaining 11 micronutrients showed no significant causal association with NMSC or MM (p > 0.05). Conclusions This study highlights that Selenium and Potassium may protect against MM, while Calcium increases NMSC risk, with Vitamin B6 providing protection against NMSC. These findings enhance our understanding of micronutrients in skin cancer mechanisms and inform potential prevention strategies.